Menopausal symptoms and quality of life in female survivors treated with hematopoietic stem cell transplantation - Su, Huina; Li, Huiling; Zhang, Hua; Yang, Xin; Wang, Chaohua (Frontiers in Psychiatry, 2023)
Objectives To assess the severity of menopausal symptoms and the correlation among different quality of life questionnaires and compare the quality of life of patients who underwent HSCT for hematological disorders with the norm group in order to facilitate personalized and directed therapeutic intervention for patients. Methods We recruited women who had POF after HSCT for hematologic diseases in the gynecological endocrinology outpatient clinic of Peking University People’s Hospital. Women with HSCT were included in the study if they had 6 months of spontaneous amenorrhea with serum follicle-stimulating hormone levels greater than 40 mIU/mL taken 4 weeks apart. During the survey, all women were required to fill out the Menopause and quality-of-life related questionnaires. We analyzed the severity of menopausal symptoms, anxiety, and depression in Participants. In addition, differences on the SF-36 scale scores between the study group and norm groups were examined. Results In total, 227 (93.41%) patients completed the survey and were analyzed. The severity of all symptoms is “none and mild” in MRS, MENQOL, GAD-7, and PHQ-9. On the MRS, the most common symptoms were irritability, physical and mental exhaustion, and sleep problems. The severest symptoms were sexual problems (53, 73.82%), followed by sleep problems (44, 19.38%) and mental and physical exhaustion (39, 17.18%). In the MENQOL, the most common symptoms were psychosocial and physical symptoms. The severest symptoms were sexual symptoms (35, 48.75%) followed by psychosocial symptoms (23, 10.13%). Moderate-severe scores were shown in 11.89% (27) and 18.72% (42) cases in the GAD-7 and PHQ-9, respectively. Based on SF-36, in comparison with the norm group, the HSCT participants had higher vitality scores and lower role physical, physical functioning, and role emotional scores aged 18-45. In addition, the HSCT participants had lower mental health scores aged 18-25, and lower general health scores aged 25-45. No strong correlation was observed between questionnaires in our study. Conclusion Overall, menopausal symptoms are milder in female patients after HSCT. There is no single scale that comprehensively assesses the patient's quality of life after HSCT. We need to assess the severity of various symptoms in patients using different scales.